2017
DOI: 10.1017/s0022377817000873
|View full text |Cite
|
Sign up to set email alerts
|

Stability of electron wave spectra in weakly magnetized plasmas

Abstract: Analytical models for nonlinear electron plasma waves in weakly magnetized plasmas are developed for single as well as multi-mode conditions, with continuous wave spectra being a limiting case. The conditions for wave decay as well as modulational instabilities are analysed. Our results demonstrate that slow or nearly stationary plasma density variations can be found for weakly magnetized plasmas even for weakly nonlinear electron plasma waves without involving cavitation of large amplitude plasma waves. A red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(224 reference statements)
0
1
0
Order By: Relevance
“…Heuristic arguments then implie that, due to nonlinear effects, the wavenumber spectra should broaden until some quasi stationary conditions are established. Analytical studies of electron plasma waves in magnetized as well as unmagnetized plasmas (Bhakta and Majumder, 1983;Pécseli, 2014;Kono and Pécseli, 2016;Kono and Pécseli, 2017a;Kono and Pécseli, 2017b) demonstrated that with the given assumptions a wide band spectrum was indeed less unstable than a narrow band. The results did not, however, predict complete modulation-or parametric decaystabilizations for wide band wavenumber spectra: this could be due to a simplifying quasi-normal (sometimes termed quasi-Gaussian) assumption (Leslie, 1973;Alber, 1978) made in the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Heuristic arguments then implie that, due to nonlinear effects, the wavenumber spectra should broaden until some quasi stationary conditions are established. Analytical studies of electron plasma waves in magnetized as well as unmagnetized plasmas (Bhakta and Majumder, 1983;Pécseli, 2014;Kono and Pécseli, 2016;Kono and Pécseli, 2017a;Kono and Pécseli, 2017b) demonstrated that with the given assumptions a wide band spectrum was indeed less unstable than a narrow band. The results did not, however, predict complete modulation-or parametric decaystabilizations for wide band wavenumber spectra: this could be due to a simplifying quasi-normal (sometimes termed quasi-Gaussian) assumption (Leslie, 1973;Alber, 1978) made in the analysis.…”
Section: Discussionmentioning
confidence: 97%